2022
DOI: 10.1021/acssuschemeng.2c02657
|View full text |Cite
|
Sign up to set email alerts
|

Superhigh-Luminance Ce:YAG Phosphor in Glass and Phosphor-in-Glass Film for Laser Lighting

Abstract: Solid laser lighting with high photoelectric conversion efficiency and compact size has been increasingly vital in lighting applications. Extensive research has been conducted to obtain high-quality color converters for application to high-power and high-luminance laser lighting. Currently, Y3Al5O12:Ce3+ phosphor in glass (Ce:PiG) and Y3Al5O12:Ce3+ phosphor-in-glass film (Ce:PiF) possessing high efficiency, low cost, easy fabrication, and controllable chromaticity are becoming the most mainstream research dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 48 publications
(87 reference statements)
1
42
0
Order By: Relevance
“…For other optical properties of the LSN PiF including QE and PL intensity provided in Figure b,c, when the temperature exceeds 1060 °C, they begin to decline. This is because the LSN:Ce phosphor will decompose when the temperature is too high and then react seriously with the glass . Consequently, the sintering temperature was kept at 1060 °C, and the holding time was changed from 10 to 20 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For other optical properties of the LSN PiF including QE and PL intensity provided in Figure b,c, when the temperature exceeds 1060 °C, they begin to decline. This is because the LSN:Ce phosphor will decompose when the temperature is too high and then react seriously with the glass . Consequently, the sintering temperature was kept at 1060 °C, and the holding time was changed from 10 to 20 min.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the light source being developed for commercial applications such as projectors and automotive headlights mainly combines blue laser diodes and Ce-doped yellow-emitting yttrium aluminum garnet (YAG:Ce). , Furthermore, the white light source which pursues high CRI and low CCT always plays a crucial part in the laser lighting field . In recent years, La 3 Si 6 N 11 :Ce 3+ (LSN:Ce), a burgeoning nitride phosphorescent material, has received a great deal of attention on account of its excellent chemical and thermal stability, and it is expected to become the potential light source of the white laser. , Compared with YAG:Ce, LSN:Ce fluorescent material can produce unique red emission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Phosphor-in-Glass technique, the low-melting glass frit should have moderate softening temperature to reduce chemically aggressive components and keep the embedded phosphor intact. 40,41 Herein, the 33B 2 O 3 -10SiO 2 -40ZnO-5Li 2 CO 3 -6La 2 O 3 -6WO 3 (in mol%) glass was chosen as the host glass considering the preparation temperature of the CsPbBr 3 –SiO 2 powder. The differential scanning calorimetry (DSC) analysis showed that the glass transition temperature ( T g ) of the host glass is 541 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8] Accumulation of large amounts of heat in the fluorescent converter, leading to the notorious thermal quenching phenomenon, which then affects the development of LD lighting. [9,10] Currently, in order to address the thermal extinction phenomenon that occurring in LD lighting for achieving better luminescence, numerous all-inorganic color converters including single-crystal phosphors , [11][12][13][14] phosphor in glasses (PiGs), [15][16][17][18] phosphor ceramics, [19][20][21] and phosphor in glass films (PiFs) [8,[22][23][24][25][26] are being extensively studied for their different properties. Among the aforementioned phosphor converters, although single-crystal phosphors and phosphor ceramics are prepared with excellent thermal stability, they are necessarily expensive due to their complicated process and high cost, which limits their popularity in the market.…”
Section: Introductionmentioning
confidence: 99%